CORRELATIONS OF TELEROENTGENOGRAPHIC PARAMETERS OF THE JAWS WITH BASIC CRANIOMETRIC PARAMETERS IN JUVENILE MEN AND JUVENILE WOMEN WITH ORTHOGNATHIC BITE AND DIFFERENT FACIAL TYPES ACCORDING TO SCHWARZ A.M. - Prokopenko, O.S.; Polishchuk, S.S.; Prokopenko, S.V.; Gunko, I.P.; Haiduk, O.A. (World of Medicine and Biology, 2023)
Peculiarities of correlations between TRG indicators of the upper and lower jaws, inter-jaw indicators, and TRG indicators of the skull in Ukrainian young men and young women with orthognathic bite with different facial types according to Schwarz A. M. were established. In young men with the first type of face (back type), the revealed reliable correlations were mostly direct strong and medium strength, in young women – almost the same number of direct and reverse correlations of medium strength. In young men with the second type of face (average type), reliable correlations were mostly direct of medium strength and strong, and in young women – mostly inverse of medium strength. In young men with the third type of face (front type), the number of direct and reverse correlations of mostly average strength did not differ significantly, and in young women, direct correlations prevailed among the average strength of correlations.